2022
DOI: 10.1111/liv.15430
|View full text |Cite
|
Sign up to set email alerts
|

CCN6 improves hepatic steatosis, inflammation, and fibrosis in non‐alcoholic steatohepatitis

Abstract: Background and Aims: CCN6 is a secretory protein with functions of maintaining mitochondrial homeostasis and anti-oxidative stress; and yet, whether it is involved in the pathogenesis of non-alcoholic steatohepatitis (NASH) is still obscure. We investigated the role and mechanism of CCN6 in the development of NASH.Methods: Human liver tissue samples were collected to detect the expression profile of CCN6. High-fat-high-cholesterol (HFHC) and methionine choline-deficient (MCD) diet were applied to mice to estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…On the contrary, CCN6 expression is downregulated in livers of experimental fatty liver disease and patients suffering from non‐alcoholic steatohepatitis (NASH), while the overexpression of CCN6 significantly attenuated hepatic steatosis, inflammation, and fibrosis in NASH mice suggesting that this CCN member has antifibrogenic activities (Song et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, CCN6 expression is downregulated in livers of experimental fatty liver disease and patients suffering from non‐alcoholic steatohepatitis (NASH), while the overexpression of CCN6 significantly attenuated hepatic steatosis, inflammation, and fibrosis in NASH mice suggesting that this CCN member has antifibrogenic activities (Song et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that CCN6–IGF‐1 interaction regulates chondrocyte hypertrophy (Repudi et al 2013). Unlike CCN3 and − 4, CCN6 expression is downregulated in the liver of experimental fatty liver disease and in patients suffering from NASH; while the overexpression of CCN6 attenuated hepatic steatosis, inflammation, and fibrosis in NASH mice suggesting that CCN6 is also anti‐fibrotic (Song et al 2023). CCN6 is a secretory protein involved in mitochondrial homeostasis and oxidative stress; a new report further studied whether it is involved in the pathogenesis of NASH (Song et al 2023).…”
Section: Ccn6/wisp3 Protects Against Hepatic Steatosis Inflammation A...mentioning
confidence: 99%
“…Unlike CCN3 and − 4, CCN6 expression is downregulated in the liver of experimental fatty liver disease and in patients suffering from NASH; while the overexpression of CCN6 attenuated hepatic steatosis, inflammation, and fibrosis in NASH mice suggesting that CCN6 is also anti‐fibrotic (Song et al 2023). CCN6 is a secretory protein involved in mitochondrial homeostasis and oxidative stress; a new report further studied whether it is involved in the pathogenesis of NASH (Song et al 2023). In human NASH patients and two murine models, wherein NASH is induced either by high‐fat‐high‐cholesterol (HFHC) or by methionine choline‐deficient (MCD) diet, hepatic CCN6 level was significantly down regulated by ≥ 25%.…”
Section: Ccn6/wisp3 Protects Against Hepatic Steatosis Inflammation A...mentioning
confidence: 99%
See 2 more Smart Citations